2, 2′- bipyridine coplanar with coordination square of Pd(II) nonyldithiocarbamato antitumor complex interacting with DNA in two distinct steps. Issue 11 (18th August 2017) - Aminzadeh, Mohammad; Mansouri-Torshizi, Hassan; Modarresi-Alam, Ali Reza
Abstract : Cisplatin is one of the most effective chemotherapy drugs, and has been widely employed for more than four decades in the treatment of different forms of human tumors. In recent years, various examples of metal complex-based compounds have been used for medicinal purposes. In this context, the novel palladium(II) complex, [Pd(non-dtc)(bpy)]NO3, (non-dtc = nonyldithiocarbamate and bpy = 2, 2′- bipyridine) has been synthesized and characterized by means of elemental analysis, conductivity measurements, FT-IR, 1 H NMR, 13 C NMR, and electronic spectroscopy studies. The 50% cytotoxic concentrations (Ic50 ) of this Pd(II) complex (0.53 mM) and cisplatin (154 mM) against human cell tumor line (K562) indicates its interaction with DNA of cancer cell at quite low concentration. Thus, binding characteristics of this compound to calf thymus DNA (CT-DNA) has been investigated by UV–vis absorption spectroscopy and fluorescence spectra. The exciting observation of this work in the UV–visible studies was that the Pd(II) complex exhibit two or more types of interaction with CT-DNA. Such properties have rarely been observed in the literature. This complex cooperatively binds with DNA and denatures it too. Fluorescence studies proved the intercalation mode of binding and the other modes seems to be hydrophobic and electrostatic interactions. Binding parameters and thermodynamics of the interaction with CT-DNA are also described. Finally, multifunctional interactions of [Pd(non-dtc)(bpy)]NO3 make it suitable to interact with DNA of cancer cell at quite low concentration and if it is used as anticancer agent, very low doses will be needed which may have fewer side effects.